PENGARUH PELATIHAN DAN GAYA KEPEMIMPINAN TERHADAP KOMPETENSI, KOMITMEN ORGANISASI, DAN KINERJA PERSONEL PADA BIRO SUMBER DAYA MANUSIA POLDA BALI - I Made Mardiawan; I Ketut Mustika (Universitas Triatma Mulya, 2020)
This study aims to analyze the effect of training and leadership style on competence, organizational commitment, and personnel performance at the Bali Police Human Resources Bureau, as well as knowing the level of influence, and identifying variables that have a dominant influence on personnel performance. This research uses a quantitative analysis approach. The samples in this study were 77 people at the Bali Police HR Bureau. The analysis technique used is Partial Least Square (PLS). Keywords: training, leadership style, competence, organizational commitment, performance.